Job insecurity, job engagement and turnover intention of Hotel employees in Yogyakarta during pandemic Covid-19 - Putranti, Latifah; Nurmasari, Nurani Desty; Sumantri, Era Manya (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2022)
The pandemic of Covid-19 disrupted all economic activities, especially the tourism industry. The Special Region of Yogyakarta, a tourism city, has been badly affected. In surviving the pandemic conditions, the hotel industry adopted policies to carry out efficiency, which had an impact on job insecurity, job engagement, and turnover intention. This study aims to examine the impact of Covid-19, the effect of job insecurity, and job engagement on turnover intention. This study was conducted in the hotel industry in the Special Region of Yogyakarta in 2022. The sample used in this study was 100 hotel employees and used a non-probability sampling technique through a purposive sampling approach. The data analysis technique in this study uses structural equation modeling (SEM). The results showed that Job engagement negatively influenced on turnover intentions. Meanwhile, Job insecurity has a positive influence on turnover intentions. Last, the job insecurity did not affect turnover intention.